Come a little closer [large type] - Garlock, Dorothy (Thorndike Press large print basic, 2012)
It's 1946, after the end of WWII, and Christina Tucker decides to take a nursing job in the small town of Longstock, Wisconsin, working with Dr. Samuel Barlow. Dr. Barlow is well-regarded by the people of Longstock, except for one man: Morris Doyle. Morris believes that his younger brother Jimmy died as a result of Barlow's shoddy care and he is determined to punish the doctor for what he's done -- even if it means hurting those the doctor loves most, including Christina Tucker.